Pemberdayaan masyarakat hidup sehat bebas vektor nyamuk melalui konsep ecohealth village berbasis education for sustainable development - Giyantolin Giyantolin; Soenarwan Hery Poerwanto; Azinuddin Ikram Hakim; Muflihah Abustani; Robi Wibowo (Riau Journal of Empowerment, 2019)
On 2018, the incidence of Dengue Hemorrhagic Fever (DHF) occurred in Sukoharjo District, which reached 42 villages with the highest in Sukoharjo District, one of which was in Kelurahan Kenep. More understanding is needed about the education of the dangers of mosquitoes, the characteristics of breeding and the formation of movements, namely through active, creative, innovative and solutive community empowerment. The establishment of the program carried out was the empowerment of mosquito-free healthy communities through the Ecohealth Village concept based on Education for Sustainable Development, which is tied to social, environmental and economic. This program is also carried out with the prevention of various perspectives, such as the use of used materials as mosquito traps, the spread of anti-mosquito plants, and movement of posters to encourage people to live mosquito-free healthy lives and the establishment of one Jumantik Monitoring Household. The results of this program influence the understanding of creative, innovative education and solutions to mosquitoes. During and post-implementation, there have been no cases of dengue. The program provides a significant influence in realising a mosquito-free healthy village.